2018
DOI: 10.1080/13880209.2018.1501705
|View full text |Cite
|
Sign up to set email alerts
|

Safranal-promoted differentiation and survival of dopaminergic neurons in an animal model of Parkinson’s disease

Abstract: Context: Safranal (SAF) is verified to have potential effects in promoting nerve growth.Objectives: This study verifies the role of SAF in promoting dopaminergic neurons growth in vitro and in vivo.Material and methods: Rat neural stem cells (NSC) were treated with 1, 20, or 100 ng/mL of SAF, and the expression levels of tyrosine hydroxylase (TH) and dopamine transporter (DAT) were assayed by flow cytometry and real-time PCR and the secretion of dopamine (DA) was assayed by ELISA. Then, 2 × 106 cells of SAF-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…RA-induced differentiated SH-SY5Y cells exhibit the dopaminergic neuron phenotype and express tyrosine hydrogenase (TH) and dopamine transporter (DAT), both of which are involved in the production of dopamine . Because we found that nAg10 inhibited RA-induced neuronal differentiation, we hypothesized that nAg10 may also inhibit the development of the dopaminergic neuron phenotype; we therefore evaluated the effect of nAg10 on dopamine production and on the expression of TH and DAT in RA-treated SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RA-induced differentiated SH-SY5Y cells exhibit the dopaminergic neuron phenotype and express tyrosine hydrogenase (TH) and dopamine transporter (DAT), both of which are involved in the production of dopamine . Because we found that nAg10 inhibited RA-induced neuronal differentiation, we hypothesized that nAg10 may also inhibit the development of the dopaminergic neuron phenotype; we therefore evaluated the effect of nAg10 on dopamine production and on the expression of TH and DAT in RA-treated SH-SY5Y cells.…”
Section: Resultsmentioning
confidence: 99%
“…RA-induced differentiated SH-SY5Y cells exhibit the dopaminergic neuron phenotype and express tyrosine hydrogenase (TH) and dopamine transporter (DAT), both of which are involved in the production of dopamine. 24 Because we found that nAg10 inhibited RA-induced neuronal differentiation, we hypothesized that nAg10 may also inhibit the development of the dopaminergic neuron phenotype; we therefore evaluated the effect of nAg10 on dopamine production and on the expression of TH and DAT in RA-treated SH-SY5Y cells. The concentration of dopamine in the culture supernatant was significantly decreased in cells treated with RA + nAg10 (0.1− 2.5 μg/mL) compared with that in the supernatant from cells treated with RA only, and the decrease was nAg10concentration-dependent (Figure 3A).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The above results indicated that Safranal alleviated the symptoms of motor disorders in Parkinson’s mouse and it may be used to treat Parkinson’s disease. Moreover, there have been two previous studies on Safranal and Parkinson’s disease, one of which was Yi Zhao et al demonstrated that Safranal promoted the production of functional DA cells and alleviated PD through in vitro and in vivo rat models [ 39 ], the other was P-K Pan et al, indicated that Safranal protected against rotenone-induced neurotoxicity associated with Nrf2 signaling pathway in vitro model of PD [ 40 ]. Surprisingly, their research was consistent with our research.…”
Section: Discussionmentioning
confidence: 99%
“…This neuroprotection was observed due to anti-apoptotic effect, down regulation of inflammatory reactions, and edema weakening in spinal cord of rats. Its nerve growth stimulation was also verified in dopamine cells and this indicated use of Safranal as a novel drug for the treatment of Parkinson's disease (PD) ( Zhao and Xi, 2018 ). This neurodegenerative disease is characterized by slow progress of dopamine (DA) neuron degeneration.…”
Section: Safranal In Neurodegerative Diseasesmentioning
confidence: 94%